Pengaruh Penggunaan Selebriti dalam Iklan terhadap Minat Beli Konsumen - Asmai Ishak (Management Development Centre (MDC) Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2008)
This study investigates the effectiveness of the celebrity’s use in the advertisement. It, specifically, analyses the effect of credibility of the celebrity on the attitude toward the advertise-ment and the purchase intention. By using structural equation modelling with one congeneric measurement approach, this study indicates that from three dimensions of celebrity’s credibility, only attractiveness does not have significant influence on the attitude toward the ads. The other two dimensions that are trustwothiness and expertise have positively and significantly affect the attitude toward the ads which in turn enhances significantly the purchase intention. Additonally, it also finds that the effect of attitude toward the ads on purchase intention is so small indicating there some factors affecting the purchase intentionKeywords: credibility of the celebrity, attractiveness, trusworthiness, expertise